THE BELIS PAYMENT TRADITION IN KEDANG BARENG MARRIAGE PRACTICES: AN ISLAMIC PERSPECTIVE - Rahma Pramudya Nawang Sari; Riyanta (UIN Antasari Banjarmasin, 2025)
This study aims to analyze the practice of paying a dowry (belis) in traditional marriages in the Kedang Bareng community of Lembata Regency and to examine its suitability from an Islamic legal perspective. The belis tradition is a form of respect for the bride's family, but its practice is often viewed as problematic if it places a heavy economic burden on the groom. This study used a qualitative approach with field research methods. Data were collected through interviews with traditional leaders, religious leaders, couples who had previously had a traditional marriage, and village officials as key informants. Data analysis was conducted using an interactive model through the stages of reduction, presentation, and conclusion drawing. The results of this study indicate that the belis in Kedang Bareng has symbolic meaning as a symbol of respect, kinship ties, and confirmation of social status. However, in practice, a high amount of belis can cause socio-economic obstacles, especially for families with limited income. From an Islamic legal perspective, the belis tradition is permitted as long as it does not conflict with the principles of justice, willingness (taradhi), and does not burden either party, as is the principle of marriage in Islam. If belis is viewed as a customary dowry that complements the dowry without eliminating its sharia obligations, then it is permissible. The implication of this research is the need for ongoing dialogue between traditional and religious leaders to adapt the practice of belis to align it more closely with the principles of maqasid al-syari'ah (the principle of Islamic law), particularly in maintaining family welfare and avoiding harm. The results of this study can also serve as a reference in formulating village policies that accommodate both customary and Islamic values ​​in marriages in the Kedang Bareng community.